Understanding the mediator role of satisfaction in public transport: A cross-country analysis. (January 2021) - de Oña, Juan
Abstract: Many studies have analyzed the relationship between service quality, satisfaction and behavioral intentions or loyalty in the field of public transport. Yet despite growing interest, there is a lack of consensus regarding a number of aspects, e.g.: the difference between service quality and satisfaction, between behavioral intentions and loyalty, or the mediating effect of satisfaction between service quality and behavioral intentions. The main objective of this article is to shed light on the type of mediator effect exerted by satisfaction between service quality and behavioral intentions or loyalty in the area of urban and metropolitan public transport. To this end, structural equation modeling (SEM) is used to compare two competitive models, one in which satisfaction plays a partial mediating role (i.e. service quality presents direct and indirect effects on behavioral intentions or loyalty), and another where satisfaction exerts a complete or full mediator effect (i.e., service quality presents only indirect effects). The comparison is based on data from a single (translated) survey of public transport users in five European cities: Madrid, Rome, Berlin, Lisbon and London. The results support the superiority of the full mediator model over the partial mediator one in the urban and metropolitan public transport sector. The use of five independent samples made it possible replicate results and generalize conclusions, as well as identify other methodological and practical aspects. From a methodological standpoint, this paper confirmed the need to consider service quality and satisfaction as different factors and to compare alternative models with different samples when applying SEM to the public transport field. From a practical standpoint, the results suggest that service quality, associated with specific attributes of service, exerts a total effect on behavioral intentions or loyalty, superior to the effect of satisfaction, a finding that has important implications for transport operators. Finally, this study confirms that in large cities, the intermodality of public transport is one of the attributes that contributes most to the appraisal of its service quality, together with frequency, punctuality and speed. Highlights: Service quality (SQ) and satisfaction (SA) are different constructs and should be measured separately. Behavioral intentions (BI) and loyalty (LO) are different constructs. However, BI and LO use indicators reflecting the intention to reutilize the service and to recommended it. SA exerts a complete mediator role between SQ and BI in urban and metropolitan public transport services. In Madrid, Rome, Berlin, Lisbon and London, SQ exerts an overall positive effect on BI, superior to the effect of SA. In large cities, intermodality is among the most important attributes contributing to SQ. Other important attributes contributing to SQ in large cities are frequency, punctuality and speed.